Mohs micrographic surgery in dermatofibrosarcoma protuberans allows tumour clearance with smaller margins and greater preservation of healthy tissue compared with conventional surgery: a study of 74 primary cases. (9th March 2015) - Serra‐Guillén, C.; Llombart, B.; Nagore, E.; Guillén, C.; Requena, C.; Traves, V.; Kindem, S.; Alcalá, R.; Rivas, N.; Sanmartín, O.
Summary Background Dermatofibrosarcoma protuberans (DFSP) is an uncommon skin tumour with aggressive local growth. Whether DFSP should be treated with conventional surgery (CS) or Mohs micrographic surgery (MMS) has long been a topic of debate. Objectives To calculate, in a large series of DFSP treated by MMS, the minimum margin that would have been needed to achieve complete clearance by CS. Secondly, to calculate the percentage of healthy tissue that was preserved by MMS rather than CS with 2‐ and 3‐cm margins. Methods The minimum margin was calculated by measuring the largest distance from the visible edge of the tumour to the edge of the definitive surgical defect. Tumour and surgical defect areas for hypothetical CS with 2‐ and 3‐cm margins were calculated using AutoCAD for Windows. Results A mean minimum margin of 1·34 cm was required to achieve complete clearance for the 74 tumours analysed. The mean percentages of skin spared using MMS rather than CS with 2‐ and 3‐cm margins were 49·4% and 67·9%, respectively. Conclusions MMS can achieve tumour clearance with smaller margins and greater preservation of healthy tissue than CS.